Cell encapsulation in thermoresponsive chitosan based hydrogels for cartilage tissue engineering - Lima, H. C. (2008)
[Excerpt] The repair of articular cartilage is still a challenging medical problem and there is a need for the development of a clinically useful cartilage tissue engineering strategies. A variety of materials have been suggested for cartilage engineered repair, and injectable hydrogels are among the most promising alternatives. This work aimed the exploration of the suitability of chitosan/ glycerol-phosphate/hydroxyethyl cellulose (CGP) hydrogel as scaffold for cell encapsulation, using ATDC5 cells (murine chondrogenic cell line) to produce cartilage-like tissue trough tissue engineering approach. [...]